An ultra-thin photosensitive resin coating and its preparation method

By applying ultra-thin photosensitive resin coating on the glasses frame, combined with ion beam spinning and electrostatic field spraying technology, the existing glasses frame coatings are solved, and the photosensitive color discoloration and yellowing resistance are achieved, which enhances the aesthetics and durability of the coating.

CN114839793BActive Publication Date: 2025-06-03YICHUN KAIQI BIOTECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210376890.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-11
Publication Date
2025-06-03
Estimated Expiration
2042-04-11

AI Technical Summary

Technical Problem

The color of the existing glasses frame coating is not clear enough, the color changes are not obvious enough, and it is easy to fall due to sweat, rain, etc., has a short service life, and has a long-term contact with ultraviolet rays, oxygen and moisture substances in the air, resulting in aging, loss of light, color loss, darkness and other disadvantages.

Method used

The ultra-thin photosensitive resin coating is used to form a copper fiber film through ion beam assisted spinning, and combined with electrostatic field assisted spraying technology, a matrix coating and a water-oxygen barrier layer are formed. The photosensitive nature of the photosensitive resin and the oxidative and devalence effect of silver ions are used to achieve color changes, and the barrier effect of the coating is enhanced through alumina and silica films.

Benefits of technology

The photosensitive color discoloration and yellowing resistance of the glasses frame coating are achieved, which enhances the aesthetics and service life of the coating, while improving the barrier effect on water and oxygen, and extends the durability of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003590662420000111
    Figure BDA0003590662420000111
Patent Text Reader

Abstract

The present invention discloses an ultra-thin photosensitive resin coating and a preparation method thereof, relating to the technical field of coating materials. First, the present invention modifies epoxy resin with 3-hydroxy-1-naphthylamine, 5-chloro-1,3,3-trimethyl-2-methylene indoline, 3-aminophthalate and silver chloride to form a photosensitive resin, enabling the coating to change with the change of light; then, ion beam assisted spinning is used to form a copper fiber film on the surface of the spectacle frame, and this is used as the cathode of the electric field. The photosensitive resin is ionized by a high-voltage electric field and deposited on the spectacle frame, and then alumina and silica films are grown layer by layer through electrostatic field assisted spraying, effectively blocking water and oxygen substances. The ultra-thin photosensitive resin coating prepared by the present invention has the effects of photosensitive color change and yellowing resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coating materials, and particularly to an ultra-thin photosensitive resin coating and a preparation method thereof. Background Art

[0002] Most of the existing spectacle frames are of a single color. Some spectacle frames with color-changing functions are only made by spraying thermochromic powder or photochromic powder on the surface of the spectacle frames. Since the color of the spectacle frames themselves is relatively dark, the colors presented after spraying the color-changing powder are not vivid enough, and the color changes are not obvious enough, resulting in low aesthetics. Moreover, the change in temperature is often very slow. For example, when going out, the temperature generally does not change much, and it is also easy to fall off when encountering sweat or rain, resulting in a short service life.

[0003] Since glasses are products that people carry with them, they are often irradiated by outdoor ultraviolet rays and come into contact with oxygen and moisture substances in the air for a long time, resulting in the aging of ordinary spectacle frames. Over time, problems such as loss of luster, loss of color, and dullness will occur, and the surface color will turn yellow. For some light-colored spectacle frames, the yellowing is more obvious, seriously affecting the aesthetics of the glasses and restricting daily use. Summary of the Invention

[0004] The purpose of the present invention is to provide an ultra-thin photosensitive resin coating and a preparation method thereof to solve the problems existing in the prior art.

[0005] To solve the above technical problems, the present invention provides the following technical solution: An ultra-thin photosensitive resin coating is obtained by the following method. Ion beam-assisted spinning is used on the spectacle frame to obtain a copper fiber membrane spectacle frame; then, with the copper fiber membrane spectacle frame as the cathode of the electric field and the nozzle as the anode, photosensitive resin is sprayed to obtain a matrix coating; and then electrostatic field-assisted spraying is carried out to obtain a water and oxygen barrier layer.

[0006] Further, the photosensitive resin is prepared from epoxy resin, 3-hydroxy-1-naphthylamine, 5-chloro-1,3,3-trimethyl-2-methylene indoline, 3-aminophthalate, and silver chloride.

[0007] Further, the water and oxygen barrier layer includes an alumina film and a silica film.

[0008] Further, a preparation method of an ultra-thin photosensitive resin coating includes the following preparation steps:

[0009] (1) Place the pretreated spectacle frame in an ion thinning instrument and evacuate to 3.2×10 -3 ~5.6×10 -3Pa. Under an argon atmosphere, bombard for 15 - 27 s at 15 - 23 °, then bombard for 8 - 17 s at 3 - 9 °. Using copper paste as the spinning solution, spin to a film layer thickness of 10 - 30 μm, dry at 40 - 50 °C for 4 - 10 h. Then, under a hydrogen atmosphere, heat from 2 - 5 °C / min to 400 - 600 °C, hold for 2 - 5 h, then heat from 1 - 3 °C / min to 650 - 800 °C, hold for 1 - 3 h, cool from 4 - 9 °C / min to 500 °C, and then naturally cool to room temperature to obtain a copper fiber membrane spectacle frame;

[0010] (2) Using the copper fiber membrane spectacle frame as the cathode and the nozzle as the anode, spray a photosensitive resin that is 0.3 - 0.7 times the mass of the copper fiber membrane spectacle frame, and cure at 30 - 50 °C for 40 - 50 h to obtain a substrate coating;

[0011] (3) Place the substrate coating in an electrostatic field with an electric field voltage of 10 - 30 kV, heat to 280 - 330 °C, spray an alumina precursor solution at 20 - 30 mL / h, with a spraying distance of 30 - 40 mm, spray for 60 - 120 s, intermittent for 180 s, spray for a total of 12 - 24 min, then dry at 90 - 120 °C for 4 - 6 h, place in a tube furnace, react at 300 - 360 °C for 1 - 3 h under a hydrogen atmosphere, then place in the same electrostatic field, spray silica sol at the same speed for 10 - 22 min, heat to 100 - 130 °C, dry for 1 - 5 min, then heat to 400 - 450 °C, and hold for 2 - 5 h to obtain an ultra-thin photosensitive resin coating.

[0012] Further, for the pre-treated spectacle frame in step (1): Wash the spectacle frame with acetone and absolute ethanol in turn for 5 - 11 min at 25 - 35 kHz.

[0013] Further, the bombardment energy of the ion thinning instrument in step (1) is 1 - 6 keV, and the argon flow rate is 20 - 30 sccm; the spinning head size is 2 - 3 mm, the flow rate is 22 - 34 mL / min, and the air gap is 18 - 30 cm.

[0014] Further, for the copper paste in step (1): Mix polyethersulfone, N-methylpyrrolidone, and polyvinylpyrrolidone in a mass ratio of 1:4:0.2 - 1:4:0.4, grind at 14 - 36 rpm for 4 - 9 h, then add copper powder that is 6 - 11 times the mass of polyethersulfone, grind at the same speed for 44 - 50 h, and then evacuate for 33 - 59 min.

[0015] Further, for the photosensitive resin in step (2):

[0016] A. Mix E-44 epoxy resin, ethylene glycol monobutyl ether, and absolute ethanol in a mass ratio of 1:0.3:0.2 to 1:0.5:0.3. Under nitrogen protection, heat the mixture to 60 - 75°C, stir until dissolved, then add 3-hydroxy-1-naphthylamine in an amount of 0.4 - 0.7 times the mass of E-44 epoxy resin. After reacting for 12 - 15 h, add an ethanol aqueous solution in an amount of 0.6 - 2.1 times the mass of E-44 epoxy resin. The mass ratio of ethanol to water in the ethanol aqueous solution is 0.25:1. Let it stand for 18 - 34 min to obtain a photosensitive resin matrix;

[0017] B. Mix the photosensitive resin matrix, sodium hydroxide, and deionized water in a mass ratio of 1:0.3:8 to 1:0.6:15. Cool it in a salt bath to -5 - 0°C, then add sodium nitrite in an amount of 0.4 - 0.7 times the mass of the photosensitive resin matrix. While stirring at 50 - 100 rpm, add sulfuric acid with a mass fraction of 42% in an amount of 2 - 6 times the mass of the photosensitive resin matrix. After reacting for 57 - 71 min, perform suction filtration, wash with deionized water until the solution pH is 6 - 7, then add methanol in an amount of 21 - 30 times the mass of the photosensitive resin matrix. Under nitrogen protection, heat it to 66 - 80°C, then add 5-chloro-1,3,3-trimethyl-2-methyleneindoline in an amount of 0.6 - 1.3 times the mass of the photosensitive resin matrix. After reacting for 8 - 14 h, concentrate it at 200 - 300 rpm and 60 - 80°C for 2 - 4 h to obtain a spirooxazine compound; Mix 3-aminophthalate, pyridine, and the spirooxazine compound in a mass ratio of 1:6:1 to 1:14:2. Stir at 100 - 200 rpm for 6 - 10 h, then concentrate it at a vacuum degree of 0.04 - 0.08 MPa and 80 - 100°C for 2 - 5 h. Then wash it successively with ethyl acetate, distilled water, and saturated brine for 5 - 10 times, and dry it at 40 - 60°C for 5 - 10 h to obtain a modified resin;

[0018] C. Mix the modified resin with methanol at 4 to 10 times the mass of the modified resin. At 20 to 30 °C, add ammonia water with a mass fraction of 25 to 28% and 0.7 to 1.4 times the mass of the modified resin at a rate of 0.5 to 1.5 mL / min. Stir and react at 50 to 100 rpm for 6 to 9 h, then cool down to 0 to 5 °C, keep warm for 0.5 to 1.5 h, filter, and then add triethylamine at 1.0 to 2.1 times the mass of the modified resin and tetrahydrofuran at 4 to 8 times the mass of the modified resin. After mixing evenly, cool down to -10 to 0 °C, add trifluoroacetic anhydride at 1.2 to 2.6 times the mass of the modified resin at a rate of 0.6 to 1.2 mL / min, keep warm and react at -10 to 0 °C for 58 to 71 min, then raise the temperature to 30 to 40 °C, keep warm and react for 2 to 5 h, distill at a vacuum of 0.04 to 0.08 MPa and 50 to 65 °C for 3 to 6 h, then add deionized water at 2 to 4 times the amount of the modified resin substance and ethyl acetate at 3 to 6 times the mass of the modified resin, separate the liquid, wash with distilled water 3 to 7 times, and distill at a vacuum of 0.05 to 0.1 MPa and 60 to 71 °C for 2 to 4 h to obtain a nitrile compound;

[0019] D. Mix the nitrile compound, silver chloride, dimethylacetamide, and 1,8-diazabicyclo[5.4.0]undec-7-ene in a mass ratio of 1:0.3:5:0.001 to 1:0.6:9:0.001. After microwave heating at 180 to 310 °C for 8 to 20 min, wash successively with deionized water, absolute ethanol, and acetone 4 to 10 times, centrifuge at 8000 to 10000 rpm for 1 to 5 min, filter, and dry at 60 to 73 °C for 2 to 6 h to obtain a preliminary photosensitive resin; Mix the preliminary photosensitive resin, diethylenetriamine, polydimethylsiloxane, n-butanol, and xylene in a mass ratio of 1:0.08:0.6:0.6 to 1:0.22:0.9:0.9 to obtain a photosensitive resin.

[0020] Further, in the alumina precursor solution in step (3): Mix aluminum nitrate, urea, and sodium chloride in a mass ratio of 1:8:3 to 1:13:7 to obtain an alumina precursor solution.

[0021] Further, in the silica sol in step (3): Mix tetraethyl orthosilicate, absolute ethanol, deionized water, and nitric acid with a mass fraction of 58% in a mass ratio of 1:1:0.2:0.02 to 1:2:1.0:0.05, heat to 50 to 60 °C, and reflux for 3 to 5 h to obtain a tetraethyl orthosilicate mixture; Add absolute ethanol at 17 to 20 times the volume of the tetraethyl orthosilicate mixture to the tetraethyl orthosilicate mixture to obtain a silica sol.

[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0023] The present invention uses a photosensitive resin as the base material and coats a water and oxygen barrier layer to prepare a coating for spectacle frames, so as to achieve the effects of photosensitive color change and yellowing resistance.

[0024] First, the amino group of 3-hydroxy-1-naphthylamine undergoes a ring-opening reaction with epoxy resin and is grafted into the epoxy resin molecule; then, under the action of sodium nitrite, a nitroso group is introduced at the ortho position of the hydroxyl group and forms a ring with 5-chloro-1,3,3-trimethyl-2-methylene indoline to form a spirooxazine compound, making the coating photosensitive. Moreover, the multi-hydroxyl characteristics of epoxy resin can improve the polarity of the spirooxazine compound, and there are more hydrogen bonds between molecules, increasing its rigidity and making the photoisomer more stable, thus prolonging the photosensitive life of the coating. Then, the amino group of 3-aminophthalate combines with the chloride ion of the spirooxazine compound. After its ester group undergoes amidation and nitrilation, it coordinates with silver chloride and self-assembles into an organic-inorganic amorphous composite network structure and is embedded therein to obtain a photosensitive resin. Under the further induction of light, the open-ring organic matter undergoes intermolecular transition to generate colored free radicals, which promote the oxidation and valence change of silver ions, achieving a color change effect, enabling the color of the spectacle frame body coated with this coating to change with the change of light intensity, increasing the interest. At the same time, the addition of silver ions can improve the light fatigue resistance of the coating and can also fade quickly in an air-insulated environment.

[0025] Secondly, the present invention uses copper powder as the raw material to form a copper fiber film on the spectacle frame by spinning. Before spinning, the spectacle frame is bombarded with ion beams. Relying on the huge energy transmitted by the incident particles, the surface atomic activity is activated, and lattice depressions appear on the surface, enabling the copper fiber film to be embedded in the spectacle frame. Taking this as the cathode of the electric field and connecting the anode to the nozzle to form a high-voltage electrostatic field, the photosensitive resin is ionized and thus electrodeposited on the surface of the spectacle frame to form a continuous structure, with a uniform, continuous and dense surface. At the same time, when the surface of the photosensitive resin dries and cures, water evaporation generates pores, forming an uneven structure with metal particles in the photosensitive resin, increasing the surface roughness of the coating, endowing the coating with good hydrophobicity, isolating the contact between water vapor and the metal frame, and making the coating have a yellowing resistance effect. Then, using the electrostatic field-assisted spraying method, an alumina precursor solution and a silica sol are sprayed in sequence to form charged particles, which decompose in the gas phase and deposit on the surface of the photosensitive resin, forming a film by a layer-by-layer growth method. The existence of the layered structure will increase the path for small molecules such as water and oxygen to diffuse in the film layer, prolonging the penetration time of small molecules, thus achieving a barrier effect and improving the yellowing resistance effect of the coating. Specific embodiments

[0026] Next, in combination with the embodiments of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0027] In order to more clearly illustrate the method provided by the present invention, the following embodiments are used for detailed description. The test methods for each index of the ultra-thin photosensitive resin coating prepared in the following embodiments are as follows:

[0028] Photosensitive color change property: Take the same mass of the example and the comparative example for the photosensitive color change effect test. After irradiating with ultraviolet light of 365 nm for 3 minutes, observe whether there is color change.

[0029] Photosensitive color change fatigue property: Take the same mass of the example and the comparative example for the photosensitive color change fatigue effect test. Continuously irradiate with ultraviolet light of 365 nm for 8 hours, with an interval of 10 hours, and cycle 5 times, then observe whether there is color change.

[0030] Yellowing resistance: Take the same mass of the example and the comparative example for the yellowing resistance effect test. Place the specimen in a pure oxygen environment with a relative humidity of 90% for 30 days, and observe whether the surface turns yellow.

[0031] Example 1

[0032] A preparation method of an ultra-thin photosensitive resin coating, the preparation method of the ultra-thin photosensitive resin coating includes the following preparation steps:

[0033] (1) At 25 kHz, wash the spectacle frame with acetone and absolute ethanol in sequence for 11 minutes to obtain a pretreated spectacle frame; place the pretreated spectacle frame in an ion thinning instrument with a bombardment energy of 1 keV, evacuate to 3.2×10 -3 Pa, introduce argon at 20 sccm, under an argon atmosphere, bombard at 15° for 15 s, and then bombard at 3° for 8 s; mix polyethersulfone, N-methylpyrrolidone and polyvinylpyrrolidone in a mass ratio of 1:4:0.2, grind at 14 rpm for 9 hours, add copper powder 6 times the mass of polyethersulfone, grind at the same speed for 50 hours, and then evacuate for 33 minutes to obtain copper paste; use the copper paste as the spinning solution, spin to a film thickness of 10 μm, dry at 40 °C for 10 hours, then under a hydrogen atmosphere, heat to 400 °C at a rate of 2 °C / min, hold for 5 hours, then heat to 650 °C at a rate of 1 °C / min, hold for 3 hours, cool to 500 °C at a rate of 4 °C / min, and then naturally cool to room temperature to obtain a copper fiber membrane spectacle frame; during the spinning process, the size of the spinneret is 2 mm, the flow rate is 22 mL / min, and the air spacing is 18 cm;

[0034] (2) Mix E-44 epoxy resin, ethylene glycol monobutyl ether, and absolute ethanol at a mass ratio of 1:0.3:0.23. Under nitrogen protection, heat the mixture to 60 °C and stir until dissolved. Then add 3-hydroxy-1-naphthylamine, which is 0.4 times the mass of E-44 epoxy resin. After reacting for 12 hours, add an ethanol aqueous solution, where the mass ratio of ethanol to water is 0.25:1 and is 0.6 times the mass of E-44 epoxy resin. Let it stand for 18 minutes to obtain the photosensitive resin matrix.

[0035] (3) Mix the photosensitive resin matrix, sodium hydroxide, and deionized water at a mass ratio of 1:0.3:8. Cool it to -5 °C in a salt bath, then add sodium nitrite, which is 0.4 times the mass of the photosensitive resin matrix. Under stirring at 50 rpm, add sulfuric acid with a mass fraction of 42%, which is 2 times the mass of the photosensitive resin matrix. After reacting for 57 minutes, perform suction filtration and wash with deionized water until the solution pH is 6. Then add methanol, which is 21 times the mass of the photosensitive resin matrix. Under nitrogen protection, heat it to 66 °C and then add 5-chloro-1,3,3-trimethyl-2-methylene indoline, which is 0.6 times the mass of the photosensitive resin matrix. After reacting for 8 hours, concentrate at 200 rpm and 60 °C for 4 hours to obtain the spirooxazine compound. Mix 3-aminophthalate, pyridine, and the spirooxazine compound at a mass ratio of 1:6:1. Stir at 100 rpm for 10 hours, then concentrate at a vacuum of 0.04 MPa and 80 °C for 2 hours. Wash it successively with ethyl acetate, distilled water, and saturated brine 5 times and dry at 40 °C for 10 hours to obtain the modified resin.

[0036] (4) Mix the modified resin with methanol, which is 4 times the mass of the modified resin. At 20 °C, add ammonia water with a mass fraction of 25%, which is 0.7 times the mass of the modified resin, at a rate of 0.5 mL / min. Stir and react at 50 rpm for 9 hours, then cool to 0 °C and keep it at this temperature for 0.5 hours. Filter, then add triethylamine, which is 1.0 times the mass of the modified resin, and tetrahydrofuran, which is 4 times the mass of the modified resin. After mixing evenly, cool to -10 °C and add trifluoroacetic anhydride, which is 1.2 times the mass of the modified resin, at a rate of 0.6 mL / min. Keep it at -10 °C and react for 58 minutes, then heat to 30 °C and keep it at this temperature for 5 hours. Distill at a vacuum of 0.04 MPa and 50 °C for 3 hours, then add deionized water, which is 2 times the mass of the modified resin, and ethyl acetate, which is 3 times the mass of the modified resin. Separate the layers and wash with distilled water 3 times. Distill at a vacuum of 0.05 MPa and 60 °C for 2 hours to obtain the nitrile compound.

[0037] (5) Mix a nitrile compound, silver chloride, dimethylacetamide, and 1,8-diazabicyclo[5.4.0]undec-7-ene in a mass ratio of 1:0.3:5:0.001. After microwave heating at 180 °C for 20 min, wash it 4 times successively with deionized water, absolute ethanol, and acetone, centrifuge at 8000 rpm for 5 min, filter, and dry at 60 °C for 6 h to obtain a preliminary photosensitive resin material. Mix the preliminary photosensitive resin material, diethylenetriamine, polydimethylsiloxane, n-butanol, and xylene in a mass ratio of 1:0.08:0.6:0.6~ to obtain a photosensitive resin;

[0038] (6) Use a copper fiber membrane spectacle frame as the cathode and a nozzle as the anode, spray a photosensitive resin that is 0.3 times the mass of the copper fiber membrane spectacle frame, and cure at 30 °C for 50 h to obtain a matrix coating;

[0039] (7) Mix aluminum nitrate, urea, and sodium chloride in a mass ratio of 1:8:3 to obtain an alumina precursor solution. Place the matrix coating in an electrostatic field with an electric field voltage of 10 kV, heat to 280 °C, spray the alumina precursor solution at a rate of 20 mL / h, with a spraying distance of 30 mm, spray for 60 s, intermittent for 180 s, and spray for a total of 24 min. Then dry at 90 °C for 6 h, place it in a tubular furnace, and react at 300 °C for 3 h under a hydrogen atmosphere. Mix tetraethyl orthosilicate, absolute ethanol, deionized water, and nitric acid with a mass fraction of 58% in a mass ratio of 1:1:0.2:0.02, heat to 50 °C, and reflux for 5 h to obtain a tetraethyl orthosilicate mixture. Add absolute ethanol that is 17 times the volume of the tetraethyl orthosilicate mixture to the tetraethyl orthosilicate mixture to obtain a silica sol. Then place it in the same electrostatic field and spray the silica sol at the same speed for 22 min. Heat to 100 °C, dry for 5 min, then heat to 400 °C and hold for 5 h to obtain an ultra-thin photosensitive resin coating.

[0040] Example 2

[0041] A method for preparing an ultra-thin photosensitive resin coating, the method for preparing the ultra-thin photosensitive resin coating includes the following preparation steps:

[0042] (1) At 30 kHz, wash the spectacle frame successively with acetone and absolute ethanol for 8 min to obtain a pretreated spectacle frame. Place the pretreated spectacle frame in an ion thinning instrument with a bombardment energy of 3 keV, evacuate to 4.4×10 -3Ar was introduced at 25 sccm. Under an argon atmosphere, it was bombarded at 19° for 21 s and then at 6° for 12 s. Polyethersulfone, N-methylpyrrolidone, and polyvinylpyrrolidone were mixed at a mass ratio of 1:4:0.3. After grinding at 25 rpm for 6.5 h, copper powder 8.5 times the mass of polyethersulfone was added, and then ground at the same speed for 47 h. After vacuuming for 46 min, a copper paste was obtained. Using the copper paste as the spinning solution, it was spun until the film layer thickness reached 230 μm. After drying at 45°C for 7 h, under a hydrogen atmosphere, it was heated to 500°C at a rate of 3°C / min, held for 3.5 h, then heated to 725°C at a rate of 2°C / min, held for 2 h, cooled to 500°C at a rate of 6°C / min, and then naturally cooled to room temperature to obtain a copper fiber membrane spectacle frame. During the spinning process, the spinneret size was 3 mm, the flow rate was 28 mL / min, and the air gap was 24 cm;

[0043] (2) E-44 epoxy resin, ethylene glycol monobutyl ether, and absolute ethanol were mixed at a mass ratio of 1:0.4:0.25. Under nitrogen protection, it was heated to 68°C and stirred until dissolved. Then, 3-hydroxy-1-naphthylamine 0.55 times the mass of E-44 epoxy resin was added. After reacting for 13.5 h, an ethanol aqueous solution 1.35 times the mass of E-44 epoxy resin was added. The mass ratio of ethanol to water in the ethanol aqueous solution was 0.25:1. After standing for 26 min, a photosensitive resin matrix was obtained;

[0044] (3) The photosensitive resin matrix, sodium hydroxide, and deionized water were mixed at a mass ratio of 1:0.45:11.5. It was cooled to -2°C in a salt bath, and then sodium nitrite 0.55 times the mass of the photosensitive resin matrix was added. Under stirring at 70 rpm, sulfuric acid with a mass fraction of 42% 4 times the mass of the photosensitive resin matrix was added. After reacting for 64 min, it was filtered by suction, washed with deionized water until the solution pH reached 6.5. Then, methanol 25.5 times the mass of the photosensitive resin matrix was added. Under nitrogen protection, it was heated to 73°C, and then 5-chloro-1,3,3-trimethyl-2-methylene indoline 0.95 times the mass of the photosensitive resin matrix was added. After reacting for 11 h, it was concentrated at 250 rpm and 70°C for 3 h to obtain a spirooxazine compound. 3-Aminophthalate, pyridine, and the spirooxazine compound were mixed at a mass ratio of 1:10:1.5. After stirring at 150 rpm for 8 h, it was concentrated at a vacuum degree of 0.06 MPa and 90°C for 3 h, and then washed 7 times with ethyl acetate, distilled water, and saturated brine in sequence, and dried at 50°C for 7.5 h to obtain a modified resin;

[0045] (4) Mix the modified resin with methanol seven times the mass of the modified resin. At 25 °C, add ammonia water with a mass fraction of 26% that is 1.05 times the mass of the modified resin at a rate of 1.0 mL / min. Stir and react at 70 rpm for 7.5 h, then cool down to 2 °C, keep warm for 1 h, filter, and then add triethylamine that is 1.55 times the mass of the modified resin and tetrahydrofuran that is six times the mass of the modified resin. After mixing evenly, cool down to -5 °C, add trifluoroacetic anhydride that is 1.9 times the mass of the modified resin at a rate of 0.9 mL / min, keep warm and react at -5 °C for 64 min, then raise the temperature to 35 °C, keep warm and react for 3.5 h, distill at a vacuum of 0.06 MPa and 58 °C for 4.5 h, then add deionized water that is three times the mass of the modified resin and ethyl acetate that is 4.5 times the mass of the modified resin, separate the liquid, wash with distilled water five times, and distill at a vacuum of 0.08 MPa and 66 °C for 3 h to obtain a nitrile compound;

[0046] (5) Mix the nitrile compound, silver chloride, dimethylacetamide, and 1,8-diazabicyclo[5.4.0]undec-7-ene in a mass ratio of 1:0.45:7:0.001. After microwave heating at 245 °C for 14 min, wash successively with deionized water, absolute ethanol, and acetone seven times, centrifuge at 9000 rpm for 3 min, filter, and dry at 67 °C for 4 h to obtain a preliminary photosensitive resin; Mix the preliminary photosensitive resin, diethylenetriamine, polydimethylsiloxane, n-butanol, and xylene in a mass ratio of 1:0.15:0.75:0.75 to obtain a photosensitive resin;

[0047] (6) Use a copper fiber membrane spectacle frame as the cathode and a nozzle as the anode, spray the photosensitive resin that is 0.5 times the mass of the copper fiber membrane spectacle frame, and cure at 40 °C for 45 h to obtain a matrix coating;

[0048] (7) Mix aluminum nitrate, urea, and sodium chloride in a mass ratio of 1:10.5:5 to obtain an alumina precursor solution; Place the matrix coating in an electrostatic field with an electric field voltage of 20 kV, heat to 305 °C, spray the alumina precursor solution at a rate of 25 mL / h, with a spraying distance of 35 mm, spray for 90 s, intermittent for 180 s, spray for a total of 18 min, then dry at 105 °C for 5 h, place it in a tubular furnace, and react at 330 °C for 2 h under a hydrogen atmosphere; Mix tetraethyl orthosilicate, absolute ethanol, deionized water, and nitric acid with a mass fraction of 58% in a mass ratio of 1:1.5:0.6:0.035, heat to 55 °C, reflux for 4 h to obtain a tetraethyl orthosilicate mixture; Add absolute ethanol that is 18.5 times the volume of the tetraethyl orthosilicate mixture to the tetraethyl orthosilicate mixture to obtain a silica sol, then place it in the same electrostatic field and spray the silica sol at the same speed, spray for 16 min, raise the temperature to 115 °C, dry for 3 min, then raise the temperature to 425 °C, and keep warm for 3.5 h to obtain an ultra-thin photosensitive resin coating.

[0049] Example 3

[0050] A preparation method of an ultra-thin photosensitive resin coating, the preparation method of the ultra-thin photosensitive resin coating comprising the following preparation steps:

[0051] (1) At 35 kHz, successively wash the spectacle frame with acetone and absolute ethanol for 5 min to obtain a pretreated spectacle frame; place the pretreated spectacle frame in an ion thinning instrument with a bombardment energy of 6 keV, evacuate to 5.6×10 -3 Pa, introduce argon at 30 sccm, under an argon atmosphere, bombard at 23° for 27 s, and then bombard at 9° for 17 s; mix polyethersulfone, N-methylpyrrolidone and polyvinylpyrrolidone in a mass ratio of 1:4:0.4, grind at 36 rpm for 4 h, add copper powder 11 times the mass of polyethersulfone, grind at the same speed for 44 h, and then evacuate for 59 min to obtain copper paste; use the copper paste as the spinning solution, spin to a film layer thickness of 30 μm, dry at 50°C for 4 h, under a hydrogen atmosphere, heat up to 600°C at a rate of 5°C / min, hold for 2 h, then heat up to 800°C at a rate of 3°C / min, hold for 1 h, cool down to 500°C at a rate of 9°C / min, and then naturally cool to room temperature to obtain a copper fiber membrane spectacle frame; during the spinning process, the size of the spinneret is 3 mm, the flow rate is 34 mL / min, and the air spacing is 30 cm;

[0052] (2) Mix E-44 epoxy resin, ethylene glycol monobutyl ether and absolute ethanol in a mass ratio of 1:0.5:0.3, under nitrogen protection, heat up to 75°C, stir until dissolved, add 3-hydroxy-1-naphthylamine 0.7 times the mass of E-44 epoxy resin, after reacting for 15 h, add an ethanol aqueous solution 2.1 times the mass of E-44 epoxy resin, the mass ratio of ethanol to water in the ethanol aqueous solution is 0.25:1, and let it stand for 34 min to obtain a photosensitive resin matrix;

[0053] (3) Mix the photosensitive resin matrix, sodium hydroxide and deionized water in a mass ratio of 1:0.6:15, cool in a salt bath to 0°C, then add sodium nitrite 0.7 times the mass of the photosensitive resin matrix, under stirring at 100 rpm, add sulfuric acid with a mass fraction of 42% 6 times the mass of the photosensitive resin matrix, after reacting for 71 min, filter by suction, wash with deionized water until the solution pH is 7, then add methanol 30 times the mass of the photosensitive resin matrix, under nitrogen protection, heat up to 80°C, then add 5-chloro-1,3,3-trimethyl-2-methylene indoline 1.3 times the mass of the photosensitive resin matrix, after reacting for 14 h, concentrate at 300 rpm and 80°C for 2 h to obtain a spirooxazine compound; mix 3-aminophthalate, pyridine and the spirooxazine compound in a mass ratio of 1:14:2, stir at 200 rpm for 6 h, then concentrate at a vacuum degree of 0.08 MPa and 100°C for 5 h, and then wash 10 times with ethyl acetate, distilled water and saturated brine respectively, and dry at 60°C for 5 h to obtain a modified resin;

[0054] (4) Mix the modified resin with methanol at a mass ratio of 10 times the mass of the modified resin. At 30 °C, add ammonia water with a mass fraction of 28% and a mass 1.4 times that of the modified resin at a rate of 1.5 mL / min. Stir and react at 100 rpm for 6 h, then cool down to 5 °C, keep warm for 1.5 h, filter, add triethylamine with a mass 2.1 times that of the modified resin and tetrahydrofuran with a mass 8 times that of the modified resin. After mixing evenly, cool down to 0 °C, add trifluoroacetic anhydride with a mass 2.6 times that of the modified resin at a rate of 1.2 mL / min, keep warm and react at 0 °C for 71 min, then heat up to 40 °C, keep warm and react for 2 h, distill at a vacuum of 0.08 MPa and 65 °C for 6 h, add deionized water with a mass 4 times that of the modified resin and ethyl acetate with a mass 6 times that of the modified resin, separate the liquid, wash with distilled water 7 times, and distill at a vacuum of 0.1 MPa and 71 °C for 4 h to obtain a nitrile compound;

[0055] (5) Mix the nitrile compound, silver chloride, dimethylacetamide, and 1,8-diazabicyclo[5.4.0]undec-7-ene in a mass ratio of 1:0.6:9:0.001. After microwave heating at 310 °C for 8 min, wash successively with deionized water, absolute ethanol, and acetone 10 times, centrifuge at 10000 rpm for 1 min, filter, and dry at 73 °C for 2 h to obtain the initial photosensitive resin material; Mix the initial photosensitive resin material, diethylenetriamine, polydimethylsiloxane, n-butanol, and xylene in a mass ratio of 1:0.22:0.9:0.9 to obtain the photosensitive resin;

[0056] (6) Use a copper fiber membrane spectacle frame as the cathode and a nozzle as the anode, spray the photosensitive resin with a mass 0.7 times that of the copper fiber membrane spectacle frame, and cure at 50 °C for 40 h to obtain a matrix coating;

[0057] (7) Mix aluminum nitrate, urea, and sodium chloride in a mass ratio of 1:13:7 to obtain an alumina precursor solution; Place the matrix coating in an electrostatic field with an electric field voltage of 30 kV, heat to 330 °C, spray the alumina precursor solution at a rate of 30 mL / h, with a spraying distance of 40 mm, spray for 120 s, intermittent for 180 s, spray for a total of 12 min, then dry at 120 °C for 4 h, place in a tubular furnace, react at 360 °C for 1 h under a hydrogen atmosphere; Mix tetraethyl orthosilicate, absolute ethanol, deionized water, and nitric acid with a mass fraction of 58% in a mass ratio of 1:2:1.0:0.05, heat to 60 °C, reflux for 3 h to obtain a tetraethyl orthosilicate mixed solution; Add absolute ethanol with a volume 20 times that of the tetraethyl orthosilicate mixed solution to the tetraethyl orthosilicate mixed solution to obtain a silica sol, then place it in the same electrostatic field, spray the silica sol at the same speed, spray for 10 min, heat up to 130 °C, dry for 2 min, then heat up to 450 °C, and keep warm for 2 h to obtain an ultra-thin photosensitive resin coating.

[0058] Comparative Example 1

[0059] The difference between Comparative Example 1 and Example 2 lies only in step (2). Step (2) is changed to: Mix E-44 epoxy resin, ethylene glycol monobutyl ether, and absolute ethanol in a mass ratio of 1:0.4:0.25. Under nitrogen protection, heat up to 68°C and stir until dissolved to obtain a photosensitive resin matrix. The remaining preparation steps are the same as those in Example 2.

[0060] Comparative Example 2

[0061] The difference between Comparative Example 2 and Example 2 lies only in step (3). Step (3) is changed to: Mix 3-aminophthalate, pyridine, and the photosensitive resin matrix in a mass ratio of 1:10:1.5. After stirring at 150 rpm for 8 h, concentrate at a vacuum of 0.06 MPa and 90°C for 3 h, then wash successively with ethyl acetate, distilled water, and saturated brine 7 times, and dry at 50°C for 7.5 h to obtain a modified resin. The remaining preparation steps are the same as those in Example 2.

[0062] Comparative Example 3

[0063] The difference between Comparative Example 3 and Example 2 lies only in the absence of steps (4) and (5). Step (3) is changed to: Mix the photosensitive resin matrix, sodium hydroxide, and deionized water in a mass ratio of 1:0.45:11.5. Cool to -2°C in a salt bath, then add sodium nitrite 0.55 times the mass of the photosensitive resin matrix. Under stirring at 70 rpm, add sulfuric acid with a mass fraction of 42% 4 times the mass of the photosensitive resin matrix. After reacting for 64 min, filter by suction, wash with deionized water until the solution pH is 6.5, then add methanol 25.5 times the mass of the photosensitive resin matrix. Under nitrogen protection, heat up to 73°C, then add 5-chloro-1,3,3-trimethyl-2-methyleneindoline 0.95 times the mass of the photosensitive resin matrix. After reacting for 11 h, concentrate at 250 rpm and 70°C for 3 h to obtain a photosensitive resin. The remaining preparation steps are the same as those in Example 2.

[0064] Comparative Example 4

[0065] The difference between Comparative Example 4 and Example 2 is that steps (1) and (6) are absent, and step (7) is changed to: spraying a photosensitive resin 0.5 times the mass of the spectacle frame onto the spectacle frame to obtain a matrix coating; mixing aluminum nitrate, urea, and sodium chloride in a mass ratio of 1:13:7 to obtain an alumina precursor solution; placing the matrix coating in an electrostatic field with an electric field voltage of 30 kV, heating to 330 °C, spraying the alumina precursor solution at a rate of 30 mL / h, with a spraying distance of 40 mm, spraying for 120 s, intermittent for 180 s, after a total spraying of 12 min, drying at 120 °C for 4 h, placing it in a tubular furnace, reacting at 360 °C for 1 h under a hydrogen atmosphere; mixing tetraethyl orthosilicate, absolute ethanol, deionized water, and nitric acid with a mass fraction of 58% in a mass ratio of 1:2:1.0:0.05, heating to 60 °C, refluxing for 3 h to obtain a tetraethyl orthosilicate mixture; adding absolute ethanol 20 times the volume of the tetraethyl orthosilicate mixture to the tetraethyl orthosilicate mixture to obtain a silica sol, then placing it in the same electrostatic field, spraying the silica sol at the same speed, spraying for 10 min, heating to 130 °C, drying for 2 min, then heating to 450 °C, and holding for 2 h to obtain an ultra-thin photosensitive resin coating. The remaining preparation steps are the same as those in Example 2.

[0066] Comparative Example 5

[0067] The difference between Comparative Example 5 and Example 2 lies in the difference in step (1). Step (1) is changed to: at 30 kHz, successively washing the spectacle frame with acetone and absolute ethanol for 8 min to obtain a pretreated spectacle frame; mixing polyethersulfone, N-methylpyrrolidone, and polyvinylpyrrolidone in a mass ratio of 1:4:0.3, grinding at 25 rpm for 6.5 h, adding copper powder 8.5 times the mass of polyethersulfone, grinding at the same speed for 47 h, and then evacuating for 46 min to obtain a copper paste; using the copper paste as a spinning solution, spinning to a film layer thickness of 230 μm, drying at 45 °C for 7 h, then in a hydrogen atmosphere, heating to 500 °C at a rate of 3 °C / min, holding for 3.5 h, then heating to 725 °C at a rate of 2 °C / min, holding for 2 h, and then cooling to 500 °C at a rate of 6 °C / min, and then naturally cooling to room temperature to obtain a copper fiber membrane spectacle frame; during the spinning process, the size of the spinneret is 3 mm, the flow rate is 28 mL / min, and the air gap is 24 cm. The remaining preparation steps are the same as those in Example 2.

[0068] Comparative Example 6

[0069] The difference between Comparative Example 6 and Example 2 is only that step (7) is absent, and the remaining preparation steps are the same as those in Example 2.

[0070] Effect Example

[0071] Table 1 below gives the performance analysis results of the ultra-thin photosensitive resin coatings of Examples 1 to 3 and Comparative Examples 1 to 6 of the present invention.

[0072] Table 1

[0073]

[0074] From the comparison of the experimental data on the color change under ultraviolet light and the color change over a long time between the examples and the comparative examples, it can be found that this product uses 3-hydroxy-1-naphthylamine and 5-chloro-1,3,3-trimethyl-2-methylene indoline to modify epoxy resin, introducing a spirooxazine group into the molecular chain of the epoxy resin, making the coating photosensitive. Moreover, the polyhydroxy characteristics of the epoxy resin can improve the polarity of the spirooxazine group, increase the rigidity, and extend the light fatigue resistance of the coating. Then, it is further modified with 3-aminophthalate and coordinated with silver chloride. Under the further induction of light, intermolecular transitions occur, generating colored free radicals, promoting the oxidation and valence change of silver ions to achieve the color change effect. At the same time, the addition of silver ions can improve the light fatigue resistance of the coating. From the comparison of the experimental data on the yellowing situation between the examples and the comparative examples, it can be found that this product first bombards and roughens the spectacle frame with an ion beam, which is beneficial for the copper fiber film to be embedded on the surface during the spinning process, so as to act as the cathode of the electrode. Utilizing the electric field effect, the photosensitive resin is electrodeposited on the surface of the spectacle frame to fill the depressions, so that they are closely connected. And when curing, the holes remaining after the evaporation of water form a rough surface with metal ions, making the coating hydrophobic and able to isolate moisture substances. Then, using the electrostatic field-assisted spraying method, alumina and silica films are grown layer by layer on the surface to block the penetration of moisture and oxygen, effectively isolating water and oxygen, and improving the yellowing resistance effect of the coating.

[0075] For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and without departing from the spirit or basic characteristics of the present invention, the present invention can be implemented in other specific forms. Therefore, from any point of view, the embodiments should be regarded as exemplary and non-limiting. The scope of the present invention is defined by the appended claims rather than the above description. Therefore, it is intended to encompass all changes falling within the meaning and scope of the equivalent elements of the claims in the present invention. Any reference signs in the claims should not be construed as limiting the claimed rights.

Claims

1. An ultra-thin photosensitive resin coating, characterized in that, the ultra-thin photosensitive resin coating is prepared by the following method: using ion beam-assisted spinning on the spectacle frame to obtain a copper fiber membrane spectacle frame; then using the copper fiber membrane spectacle frame as the cathode of the electric field and the nozzle as the anode to spray the photosensitive resin to obtain a matrix coating; and then using electrostatic field-assisted spraying to obtain a water and oxygen barrier layer; The preparation method of the photosensitive resin is as follows: A. Mix E-44 epoxy resin, ethylene glycol monobutyl ether and absolute ethanol in a mass ratio of 1:0.3:0.2 to 1:0.5:0.

3. Under nitrogen protection, heat up to 60-75°C, stir until dissolved, then add 3-hydroxy-1-naphthylamine which is 0.4-0.7 times the mass of E-44 epoxy resin. After reacting for 12-15 hours, add an ethanol aqueous solution which is 0.6-2.1 times the mass of E-44 epoxy resin. The mass ratio of ethanol to water in the ethanol aqueous solution is 0.25:1, and let it stand for 18-34 minutes to obtain a photosensitive resin matrix; B. Mix the photosensitive resin matrix, sodium hydroxide and deionized water in a mass ratio of 1:0.3:8 to 1:0.6:

15. Cool it in a salt bath to -5-0°C, then add sodium nitrite which is 0.4-0.7 times the mass of the photosensitive resin matrix. Under stirring at 50-100 rpm, add sulfuric acid with a mass fraction of 42% which is 2-6 times the mass of the photosensitive resin matrix. After reacting for 57-71 minutes, filter by suction, wash with deionized water until the pH of the solution is 6-7, then add methanol which is 21-30 times the mass of the photosensitive resin matrix. Under nitrogen protection, heat up to 66-80°C, then add 5-chloro-1,3,3-trimethyl-2-methylene indoline which is 0.6-1.3 times the mass of the photosensitive resin matrix. After reacting for 8-14 hours, concentrate at 200-300 rpm and 60-80°C for 2-4 hours to obtain a spirooxazine compound; Mix 3-aminophthalate, pyridine and the spirooxazine compound in a mass ratio of 1:6:1 to 1:14:2, stir at 100-200 rpm for 6-10 hours, then concentrate at a vacuum degree of 0.04-0.08 MPa and 80-100°C for 2-5 hours, and then wash 5-10 times with ethyl acetate, distilled water and saturated brine respectively, and dry at 40-60°C for 5-10 hours to obtain a modified resin; C. Mix the modified resin with methanol at 4 - 10 times the mass of the modified resin. At 20 - 30 °C, add ammonia water with a mass fraction of 25 - 28% and 0.7 - 1.4 times the mass of the modified resin at a rate of 0.5 - 1.5 mL / min. Stir and react at 50 - 100 rpm for 6 - 9 h, then cool down to 0 - 5 °C, keep warm for 0.5 - 1.5 h, filter, and then add triethylamine at 1.0 - 2.1 times the mass of the modified resin and tetrahydrofuran at 4 - 8 times the mass of the modified resin. After mixing evenly, cool down to -10 - 0 °C, add trifluoroacetic anhydride at 1.2 - 2.6 times the mass of the modified resin at a rate of 0.6 - 1.2 mL / min, keep warm and react at -10 - 0 °C for 58 - 71 min, then heat up to 30 - 40 °C, keep warm and react for 2 - 5 h, distill at a vacuum of 0.04 - 0.08 MPa and 50 - 65 °C for 3 - 6 h, then add deionized water at 2 - 4 times the mass of the modified resin and ethyl acetate at 3 - 6 times the mass of the modified resin, separate the liquid, wash with distilled water 3 - 7 times, and distill at a vacuum of 0.05 - 0.1 MPa and 60 - 71 °C for 2 - 4 h to obtain the nitrile compound; D. Mix the nitrile compound, silver chloride, dimethylacetamide, and 1,8 - diazabicyclo[5.4.0]undec - 7 - ene in a mass ratio of 1:0.3:5:0.001 - 1:0.6:9:0.

001. After microwave heating at 180 - 310 °C for 8 - 20 min, wash with deionized water, absolute ethanol, and acetone 4 - 10 times in sequence, centrifuge at 8000 - 10000 rpm for 1 - 5 min, filter, and dry at 60 - 73 °C for 2 - 6 h to obtain the preliminary photosensitive resin; Mix the preliminary photosensitive resin, diethylenetriamine, polydimethylsiloxane, n - butanol, and xylene in a mass ratio of 1:0.08:0.6:0.6 - 1:0.22:0.9:0.9 to obtain the photosensitive resin.

2. A kind of ultra - thin photosensitive resin coating according to claim 1, characterized in that, the water - oxygen barrier layer comprises an alumina film and a silica film.

3. A preparation method of an ultra - thin photosensitive resin coating, characterized in that, it includes the following preparation steps: (1) Place the pretreated spectacle frame in an ion thinning instrument, evacuate to 3.2×10 -3 ~5.6×10 -3 Pa. Under an argon atmosphere, bombard at 15~23° for 15~27 s, then bombard at 3~9° for 8~17 s. Then, using copper paste as the spinning solution, spin to a film layer thickness of 10~30 μm, dry at 40~50°C for 4~10 h. Then, under a hydrogen atmosphere, heat at 2~5°C / min to 400~600°C, hold for 2~5 h, then heat at 1~3°C / min to 650~800°C, hold for 1~3 h, cool at 4~9°C / min to 500°C, and then naturally cool to room temperature to obtain a copper fiber membrane spectacle frame; (2) Using a copper fiber membrane spectacle frame as the cathode and a nozzle as the anode, spray the photosensitive resin at 0.3 - 0.7 times the mass of the copper fiber membrane spectacle frame, and cure at 30 - 50 °C for 40 - 50 h to obtain the matrix coating; (3) Place the matrix coating in an electrostatic field with an electric field voltage of 10 - 30 kV, heat to 280 - 330 °C, spray the alumina precursor solution at a rate of 20 - 30 mL / h, the spraying distance is 30 - 40 mm, spray for 60 - 120 s, with an intermittent time of 180 s, spray for a total of 12 - 24 min, then dry at 90 - 120 °C for 4 - 6 h, place it in a tubular furnace, react at 300 - 360 °C for 1 - 3 h under a hydrogen atmosphere, then place it in the same electrostatic field, spray the silica sol at the same speed for 10 - 22 min, heat up to 100 - 130 °C, dry for 1 - 5 min, then heat up to 400 - 450 °C, and keep warm for 2 - 5 h to obtain the ultra - thin photosensitive resin coating; The preparation method of the photosensitive resin is as follows: A. Mix E-44 epoxy resin, ethylene glycol monobutyl ether, and absolute ethanol in a mass ratio of 1:0.3:0.2 to 1:0.5:0.

3. Under nitrogen protection, heat to 60-75°C, stir until dissolved, then add 3-hydroxy-1-naphthylamine in an amount 0.4-0.7 times the mass of E-44 epoxy resin. After reacting for 12-15 h, add an ethanol aqueous solution in an amount 0.6-2.1 times the mass of E-44 epoxy resin. The mass ratio of ethanol to water in the ethanol aqueous solution is 0.25:

1. Let it stand for 18-34 min to obtain the photosensitive resin matrix; B. Mix the photosensitive resin matrix, sodium hydroxide, and deionized water in a mass ratio of 1:0.3:8 to 1:0.6:

15. Cool to -5-0°C in a salt bath, then add sodium nitrite in an amount 0.4-0.7 times the mass of the photosensitive resin matrix. Under stirring at 50-100 rpm, add sulfuric acid with a mass fraction of 42% in an amount 2-6 times the mass of the photosensitive resin matrix. After reacting for 57-71 min, perform suction filtration, wash with deionized water until the solution pH is 6-7, then add methanol in an amount 21-30 times the mass of the photosensitive resin matrix. Under nitrogen protection, heat to 66-80°C, then add 5-chloro-1,3,3-trimethyl-2-methylene indoline in an amount 0.6-1.3 times the mass of the photosensitive resin matrix. After reacting for 8-14 h, concentrate at 200-300 rpm and 60-80°C for 2-4 h to obtain the spirooxazine compound; Mix 3-aminophthalate, pyridine, and the spirooxazine compound in a mass ratio of 1:6:1 to 1:14:

2. Stir at 100-200 rpm for 6-10 h, then concentrate at a vacuum of 0.04-0.08 MPa and 80-100°C for 2-5 h. Then wash successively with ethyl acetate, distilled water, and saturated brine 5-10 times, and dry at 40-60°C for 5-10 h to obtain the modified resin; C. Mix the modified resin with methanol in an amount 4-10 times the mass of the modified resin. At 20-30°C, add ammonia water with a mass fraction of 25-28% in an amount 0.7-1.4 times the mass of the modified resin at a rate of 0.5-1.5 mL / min. Stir and react at 50-100 rpm for 6-9 h, then cool to 0-5°C and keep warm for 0.5-1.5 h. Filter, then add triethylamine in an amount 1.0-2.1 times the mass of the modified resin and tetrahydrofuran in an amount 4-8 times the mass of the modified resin. After mixing evenly, cool to -10-0°C, and add trifluoroacetic anhydride in an amount 1.2-2.6 times the mass of the modified resin at a rate of 0.6-1.2 mL / min. Keep warm and react at -10-0°C for 58-71 min, then heat to 30-40°C and keep warm and react for 2-5 h. Distill at a vacuum of 0.04-0.08 MPa and 50-65°C for 3-6 h, then add deionized water in an amount 2-4 times the mass of the modified resin and ethyl acetate in an amount 3-6 times the mass of the modified resin. Separate the liquid, wash with distilled water 3-7 times, and distill at a vacuum of 0.05-0.1 MPa and 60-71°C for 2-4 h to obtain the nitrile compound; D. Mix a nitrile compound, silver chloride, dimethylacetamide, and 1,8-diazabicyclo[5.4.0]undec-7-ene in a mass ratio of 1:0.3:5:0.001 to 1:0.6:9:0.

001. After microwave heating at 180 - 310 °C for 8 - 20 min, wash it successively with deionized water, absolute ethanol, and acetone 4 - 10 times, centrifuge at 8000 - 10000 rpm for 1 - 5 min, filter, and dry at 60 - 73 °C for 2 - 6 h to obtain a preliminary photosensitive resin. Mix the preliminary photosensitive resin, diethylenetriamine, polydimethylsiloxane, n-butanol, and xylene in a mass ratio of 1:0.08:0.6:0.6 to 1:0.22:0.9:0.9 to obtain the photosensitive resin.

4. A method for preparing an ultra-thin photosensitive resin coating according to claim 3, characterized in that, for the pre-treated spectacle frame in step (1): Wash the spectacle frame successively with acetone and absolute ethanol for 5 - 11 min at 25 - 35 kHz.

5. A method for preparing an ultra-thin photosensitive resin coating according to claim 3, characterized in that, the bombardment energy of the ion milling machine in step (1) is 1 - 6 keV, and the argon gas flow rate is 20 - 30 sccm; the spinneret size is 2 - 3 mm, the flow rate is 22 - 34 mL / min, and the air gap is 18 - 30 cm.

6. A method for preparing an ultra-thin photosensitive resin coating according to claim 3, characterized in that, for the copper paste in step (1): Mix polyethersulfone, N-methylpyrrolidone, and polyvinylpyrrolidone in a mass ratio of 1:4:0.2 to 1:4:0.

4. After grinding at 14 - 36 rpm for 4 - 9 h, add copper powder 6 - 11 times the mass of polyethersulfone, and grind at the same speed for 44 - 50 h, then evacuate for 33 - 59 min.

7. A method for preparing an ultra-thin photosensitive resin coating according to claim 3, characterized in that, for the aluminum oxide precursor solution in step (3): Mix aluminum nitrate, urea, and sodium chloride in a mass ratio of 1:8:3 to 1:13:7 to obtain the aluminum oxide precursor solution.

8. A method for preparing an ultra-thin photosensitive resin coating according to claim 3, characterized in that, for the silica sol in step (3): Mix tetraethyl orthosilicate, absolute ethanol, deionized water, and nitric acid with a mass fraction of 58% in a mass ratio of 1:1:0.2:0.02 to 1:2:1.0:0.05, heat to 50 - 60 °C, and reflux for 3 - 5 h to obtain a tetraethyl orthosilicate mixture; add absolute ethanol 17 - 20 times the volume of the tetraethyl orthosilicate mixture to the tetraethyl orthosilicate mixture to obtain the silica sol.

Citation Information

Patent Citations

  • Photochromic spectacle bracket

    CN104238138A

  • Photochromic spectacle frame processing method, photochromic spectacle frame and spectacles

    CN113304981A